State-dependent migratory timing of postspawned Atlantic salmon (Salmo salar) - Halttunen, Elina; Jensen, Jenny; Næsje, Tor; Davidsen, Jan Grimsrud; Thorstad, Eva Bonsak; Chittenden, Cedar; Hamel, Sandra; Primicerio, Raul; Rikardsen, Audun H. (Canadian Journal of Fisheries and Aquatic Sciences, 2013)
Atlantic salmon (Salmo salar) often survive spawning and migrate back to the sea to feed, either shortly after spawning in autumn or the following spring. We conducted a 4-year observational field study using telemetry to evaluate the determinants of migration timing in Atlantic salmon postspawners (kelts). We found that individuals with low energy reserves migrated early to the risky but productive marine habitat, whereas individuals with greater energy reserves stayed in the safe but less productive river habitat until staying became energetically more costly than migrating. For males, the likelihood of overwintering in the river instead of migrating in autumn increased 27-fold with each increase in body condition index, whereas almost all females overwintered in the river. Among spring migrants, body condition was the strongest determinant of migration timing, and females left the river about 5 days later than males. Our study suggests that migration timing in Atlantic salmon kelts is the outcome of adaptive state-dependent habitat use, related to individual and sexual differences in energy allocation during spawning.